Study of students' experiences of air conditioning practices in vocational education. Issue 4 (April 2020) - Berman, E T; Hamidah, I; Mulyanti, B; Setiawan, A
Abstract: The purpose of this study is to determine the experience of students doing air conditioning practicum in vocational education. Practicum activities which are the focus of this research are practicum objectives, preparation of practicum, conditions and number of practicum tools, practicum time, practicum implementation process, competence of lecturers and laboratory assistants, and practicum evaluations. This study used a qualitative method with research participants being students in the refrigeration and air conditioning expertise at a state university in Bandung. The informants involved in this study were seven students who had carried out the air conditioning practicum for in-depth interviews. The FGD (focus group discussion) interview method is used to get general information and individual interviews to get more specific data. The results of this study are expected to provide accurate information about the practicability of student practicum so that better improvements can be made in the future. The implementation of an ideal practicum will support students to develop hands-on and minds-on.